PSIKOEDUKASI KELUARGA DALAM MENINGKATKAN KEMAMPUAN MERAWAT PENDERITA SKIZOFRENIA (Literature Review) - Titi Alfiani; Iva Puspaneli (Jurnal Ilmiah Keperawatan, 2022)
Background: Schizophrenia is a severe mental disorder in the form of difficulty thinking, communicating, interpreting reality, feeling, and showing emotions. Families with schizophrenia are an important part of the patient's recovery process. Family support is needed by people with schizophrenia in motivating them during treatment and treatment. Family psychoeducation is a family mental health treatment therapy by providing information and education through therapeutic communication. Objective: To make a conclusion based on evidence-based findings that discuss the influence of family psychoeducation in improving the ability to care for people with schizophrenia. Method: The method used in this article uses a literature review of the results of 2015-2019 research that has been published in electronic media such as ProQuest, Science Direct, CINAHL, and Pubmed. The number of Randomized controlled trials (RCTs) research articles obtained was only 9 articles that met the criteria. The keywords used are family psychoeducation, schizophrenia, treatment, ability to care. Results: The results of the study obtained that the application of family psychoeducation provides better results to help improve the family's ability to treat schizophrenics and prevent a recurrence. Conclusion: This review concludes that family psychoeducation is recommended to be used to improve the family's ability to care for people with schizophrenia so as to prevent a recurrence. The application of family psychoeducation can be done as one of the interventions for the family and is an easy, simple, and inexpensive professional nursing practice carried out by nurses independently.